A RAINHA DOS CÁRCERES DA GRÉCIA: IMAGENS DO EXÍLIO - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2017)
The present dissertation aims to explore some images that appear inside the novel A rainha dos cárceres da Grécia, by Osman Lins, published in 1976. From the archaeological landscape in Nazca, Peru, and some excerpts from Alice in Wonderland, we discuss issues concerning to the exile, as impossibility of the subject definition and expression, in the writing. We go through themes such as obscurity, marginality, the sight position, disappearance, paradox, among others. As theoretical basis, we mainly reach for Jean-Luc Nancy, Michel Foucault, Philippe Lacoue-Labarthe and Maurice Blanchot. Our reading was able to notice, in the novel, the oscilation between opposites, the remaining of the paradox and the questioning about the subject as an entire thing. We detected, also, Osman Lins‘ struggle in writing the ones with no voice, in discussing the visibility of the brazilian writer and defending a literary criticism as marginal action, which demands an investment of life, more than scientific posture.
Keywords: Exílio; Osman Lins; Literatura brasileira; Crítica literária; Exile; Osman Lins; Brazilian literature; Literary criticism; CNPQ::LINGUISTICA, LETRAS E ARTES